Acute myeloid leukemia, secondary to myelodysplastic syndrome, debuting as thrombotic thrombocytopenic purpura: case report - Huerta Velázquez, Jose Miguel (International Journal of Research in Medical Sciences, 2022)
We present a case of myelodysplastic syndrome (MDS) that progressed to acute myeloid leukemia (AML) with changes related to myelodysplasia that presented as thrombotic thrombocytopenic purpura (TTP). After a failure in response to plasmapheresis therapy and a poor long-term prognosis, the family opted for palliative care, the patient dying on the eleventh day of hospitalization. The case is an extremely rare presentation of a rare condition, as it is the second reported case of AML with myelodysplasia-related changes presenting as TTP, and the first reported case of TTP secondary to AML secondary to MDS.